EVALUATION OF SERUM INTERLEUKIN-1BETA AND INTERLEUKIN-6 LEVELS IN PATIENTS WITH CHRONIC PERIODONTITIS IN RELATION TO ATHEROSCLEROTIC HEART DISEASE - Mohammad Hussein Al-Aubaidee; Ahmed L. Azzawi; Hasan N Alabbasy (Scholar Express Journals, 2022)
Periodontitis and Atherosclerotic diseases are highly widespread diseases characterized by chronic inflammatory process.Through the last years, there has been an increase attention on the effect of oral health on atherosclerosis and other cardiovascular disease
Keywords: Atherosclerosis Heart disease, chronic periodontitis